Regulation of the expression of nitric oxide synthase and leishmanicidal activity by glycoconjugates of Leishmania lipophosphoglycan in murine macrophages. - Proudfoot, L (1996)
Lipophosphoglycan (LPG) glycoconjugates from promastigotes of Leishmania were not able to induce the expression of the cytokine-inducible nitric oxide synthase (iNOS) by the murine macrophage cell line, J774. However, they synergize with interferon gamma to stimulate the macrophages to express high levels of iNOS. This synergistic effect was critically time-dependent. Preincubation of J774 cells with the LPG glycans 4-18 h before stimulation with interferon gamma resulted in a significant reduction in the expression of iNOS mRNA and of NO synthesis, compared with cells preincubated with culture medium alone. The regulatory effect on the induction of iNOS by LPG is located in the LPG phosphoglycan disaccharide backbone. Synthetic fragments of this backbone had a similar regulatory effect on NO synthesis. Further, the production of NO by activated macrophages in the present system was correlated directly with the leishmanicidal capacity of the cells. These data therefore demonstrate that LPG glycoconjugates have a profound effect on the survival of Leishmania parasites through their ability to regulate the expression of iNOS by macrophages.